Wind energy handbook - Burton, Tony, 1947-; Jenkins, Nick, 1954-; Sharpe, David; Bossanyi, Ervin; Graham, Michael (John Wiley & Sons, Inc., 2021)
"Fully revised and updated, this third edition addresses key developments in the wind technology since the second edition was published in 2011. Completely new sections on model predictive control; use of estimators for fault detection and fatigue monitoring; active power control; and wind farm control. After a brief introduction, the authors discuss the wind resource. Particular reference is made to wind turbulence due to its importance in wind turbine design. A discussion on the basis of the aerodynamics of horizontal axis wind turbines follows, incorporating general momentum theory and dynamic stall, and an analysis of their performance. The book goes on to assess the requirements for establishing design loads. Burton et al. also set out the various design options for horizontal axis wind turbines, discussing variable speed operation and reviewing alternative blade materials and their properties. They explain the functions of the wind turbine controller and describe some of the possible analysis techniques. The text also reviews the development of wind energy projects with particular emphasis on environmental impact, and considers how wind turbines interact with the electrical power system."--